Қарақалпақстан ойконимлериниң номинациясында негативлик принципи (SCIENCE and SOCIETY, 2022)
The article analyzes the process of naming toponyms, including oikonyms, which take into account the human factor and the princi- ples of naming. In particular, the principle of negativity in the nomination of oikonyms, the transformation of small details into the main character - a motive, is explained using the example of local toponyms. On this occasion, the opinions of Russian and Uzbek scientists